Physical exercise behavior characteristics and influencing factors for participation in police officers - Feng, Yuliang; Chen, Chao; Liu, Yang; Li, Sen (Frontiers in Public Health, 2025)
ObjectiveThe purpose of this study was to analyze police officers’ exercise participation behavior and influencing factors in order to better promote physical exercise participation and improve the health status of the police force.MethodsPolice officers (n = 3,682) were recruited from 16 district public security substations in a city in eastern China to investigate their physical exercise participation and influencing factors, and logistic regression analysis was used to investigate three aspects: exercise behavior, health cognition, and influencing factors.FindingsThe physical exercise behavior of police officers showed long duration of time, but low frequency and intensity. The exercise programs were diverse but mainly involved running. The exercise motivation was mainly to keep fit and for stress relief. Logistic regression analysis indicated that source of police entry (OR = 1.467, 95% CI: 1.338–1.609), exercise conditions in the workplace (OR = 1.069, 95% CI: 1.051–1.088), exercise conditions near home (OR = 1.123, 95% CI: 1.047–1.205), high volume physical labor during work resulting in little time for exercise (OR = 1.372, 95% CI: 1.038–1.813), lack of organization (OR = 1.415, 95% CI: 1.164–1.720), economic condition constraints (OR = 1.439, 95% CI: 1.114–1.858), and weather restrictions (OR = 2.929, 95% CI: 2.418–3.548) were the main factors influencing police physical exercise behavior.ConclusionVarious influencing factors and the nature of actual police work presented barriers to police officers’ participation in physical exercise. Interventions to increase physical exercise participation would promote the physical health of police officers.